Alexithymia and somatization in psychiatric and medical patients - Salleh, Mohd Razali; Yunus, Nik Noor Azmi Mohd; Kumaraswamy, N (2001)
315 subjects comprising of equal number of psychiatric and medical patients; and control group were randomly selected for the study. Neuroses and depressive illness of the psychiatric group was chosen through psychiatric clinic. The medical outpatients attending physician clinic formed the medical group while the control group was identified from staff and patients relatives. The selected patient was administered a series of questionnaires such as Toronto Alexithymia Scale (TAS), Middlesex Hospital Questionnaires (MHQ) and Duke Health Profile (DUKE) after the diagnosis was confirmed. The psychiatric patient was further evaluated using Hamilton Depression Rating Scale (HDS) and Hamilton Anxiety Rating Scale (HAS) for assessment of severity of depression and anxiety respectively.172 (55%) subjects had positive TAS score and consider as alexithymia. The prevalence of alexithymia was significantly higher in psychiatric and medical patients than the control group. The number of alexithymia among patients with underlying depression and anxiety were significantly increased. In general individual with alexithymia had significantly higher number of personality trait than healthy volunteer. There were marked psychosocial impairments and physical disability in psychiatric and medical patients respectively. However the difference was small and did not reach the level of significant. Although we cannot link alexithymia with a specific factor, most likely it is the product of personality disturbances aggravated by medical and psychiatric illness, especially depression and anxiety.